2021
DOI: 10.1002/chem.202103012
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Highly Efficient Blue OLEDs with External Quantum Efficiencies up to 7.5 % Based on Anthracene Derivatives

Abstract: Acquiring desirable device performance with deepblue color purity that fulfills practical application requirements is still a challenge. Bipolar fluorescent emitters with hybrid local and charge transfer (HLCT) state may serve to address this issue. Herein, by inserting anthracene core in the deep-blue building blocks, the authors successfully developed two highly twisted D-π-A fluorescent emitters, ICz-An-PPI and IP-An-PPI, featuring different acceptor groups. Both exhibited superb thermal stabilities, high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…1 H NMR and 13 C NMR spectra were measured on a Bruker AVANCE III (400 MHz) spectrometer where tetramethyl silane was used as an internal reference for chloroform deuteride. Ultraviolet-visible (UV-vis) absorption and photoluminescence (PL) spectra were recorded on a Thermo Evolution 300 and a FluoroMax-4 spectrophotometer, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR and 13 C NMR spectra were measured on a Bruker AVANCE III (400 MHz) spectrometer where tetramethyl silane was used as an internal reference for chloroform deuteride. Ultraviolet-visible (UV-vis) absorption and photoluminescence (PL) spectra were recorded on a Thermo Evolution 300 and a FluoroMax-4 spectrophotometer, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…† The synthesized FlCz and SFCz (Fig. 1a) were fully characterized by MALDI-TOF mass spectroscopy, 1 H NMR spectroscopy, and 13 C NMR spectroscopy (Fig. S2-S6, ESI †).…”
Section: Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Since TTA molecules based on 4-cyanophenyl anthracene fragment have been fully investigated, in this work, we would like to propose a new approach for designing anthracene-based deep-blue TTA emitters. 15 Hence, two new anthracene derivatives, namely HO-PIAC and PIAC , were specifically designed and successfully synthesized (Scheme 1). In these models, the anthracene as a TTA core was asymmetrically functionalized at the 9,10 positions with ( N -phenylcarbazol-3-yl)phenyl and two different tetraphenylimidazoles.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In the past decade, numerous multifunctional D-A type bipolar materials have been developed as deep-blue emitters for FOLEDs and as hosts for PhOLEDs. [29][30][31][32] Among them, electron-deficient units such as pyridine, 33 phenantroimidazole, 34,35 cyano 25,44 and anthracene 36 were widely employed for the preparation of deep-blue luminogens. Tang et al recently reported four twisted D-A type deep-blue fluorophores by employing electron-deficient 1-phenyl-1H-imidazo-[4,5-c]pyridine and various electron-rich moieties.…”
Section: Introductionmentioning
confidence: 99%